Bryoflora from the Intervales State Park, São Paulo, Brazil: an important area for the biodiversity conservation of the Brazilian Southeastern Atlantic forest - Visnadi, Sandra Regina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
The Intervales State Park, together with other protected areas form the Ecological Continuum of Paranapiacaba, which is one of the seven largest continuous areas of the Brazilian Atlantic forest. The paper aims to show the richness of the bryoflora, because it list 199 species (90%) in addition of the 21 species already recorded in literature for PEI, totalizing 220 species for the hillside Atlantic forest (ombrophilous dense forest) of this park. The material totalizes 767 exsiccate, which are deposited in the Maria Eneyda Pacheco Kauffmann Fidalgo Herbarium, of the São Paulo Botanical Institute (SP). The bryoflora from PEI is rich and characteristic of the hillside Atlantic Forest of the São Paulo state, but with some species restricted to the park, not occurring in this ecosystem of other São Paulo localities; it includes two new records for Brazil (Chryso-hypnum squarrosulum, Leskeodon andicola) and five for São Paulo (Fissidens dendrophilus, Macromitrium longifolium, Orthostichopsis praetermissa, Pelekium scabrosulum, and Thamniopsis cruegeriana), besides having 13 endemic species from Brazil and one species, which in Brazil is restricted to the São Paulo state. These data demonstrate the importance of the PEI in the conservation and protection of the bryophytes diversity of the site, São Paulo state and Brazil.